2018
DOI: 10.5114/amscd.2018.77011
|View full text |Cite
|
Sign up to set email alerts
|

Methods to prevent development of adductor muscle contraction during transurethral resection of lateral bladder wall tumors

Abstract: Introduction: Adductor muscle contraction may develop due to an electrical stimulus during transurethral resection of bladder tumors (TURBT), and thus bladder wall perforation and vessel-nerve injuries may develop. Studies in the literature demonstrated that obturator nerve block (ONB) was performed with high success and low complication rates to prevent adductor muscle contraction by both urologists and anesthesiologists. However, we found no data suggesting how frequently ONB was used in current practice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In our study, significant obturator nerve reflex was observed in 2% of cases. There are many possible methods to decrease this risk under debate [25]. One of them is the use of bipolar resection instead of monopolar.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, significant obturator nerve reflex was observed in 2% of cases. There are many possible methods to decrease this risk under debate [25]. One of them is the use of bipolar resection instead of monopolar.…”
Section: Discussionmentioning
confidence: 99%